2009
DOI: 10.1002/chem.200802563
|View full text |Cite
|
Sign up to set email alerts
|

Organic Super‐Acceptors with Efficient Intramolecular Charge‐Transfer Interactions by [2+2] Cycloadditions of TCNE, TCNQ, and F4‐TCNQ to Donor‐Substituted Cyanoalkynes

Abstract: Rivaling the best one: Thermal [2+2] cycloadditions of TCNE, TCNQ, and F(4)-TCNQ to N,N-dimethylanilino-substituted cyanoalkynes afforded a new class of organic super-acceptors featuring efficient intramolecular charge-transfer interactions. These acceptors rival the acceptor F(4)-TCNQ in the propensity for reversible electron uptake as well as in electron affinity (see figure), which makes them interesting as p-type dopants for potential application in optoelectronic devices.Thermal [2+2] cycloadditions of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 85 publications
(96 reference statements)
5
76
0
4
Order By: Relevance
“…A similar result was observed for the postfunctionalization of polythiophene derivatives [25]. This study also suggested that the use of stronger acceptor molecules, such as 7,7,8,8-tetracyanoquinodimethane (TCNQ) and its derivatives [26][27][28][29][30][31][32][33][34], is effective for the dramatic lowering of the LUMO levels or the enhancement of the n-type characteristics.…”
Section: Introductionsupporting
confidence: 76%
“…A similar result was observed for the postfunctionalization of polythiophene derivatives [25]. This study also suggested that the use of stronger acceptor molecules, such as 7,7,8,8-tetracyanoquinodimethane (TCNQ) and its derivatives [26][27][28][29][30][31][32][33][34], is effective for the dramatic lowering of the LUMO levels or the enhancement of the n-type characteristics.…”
Section: Introductionsupporting
confidence: 76%
“…[ 2 ] In contrast, comparatively little effort has been focused on the development of non-fullerene small molecule acceptors. [12][13][14][15][16][17] The highest reported effi ciency of a non-fullerene with the donor polymer P3HT is only 2%. [ 14 ] This raises the question: are fullerenes and their derivatives the ultimate electron accepting compounds for use in OPV?…”
Section: Introductionmentioning
confidence: 95%
“…The compound shows two well-dened reversible one-electron reduction steps with the rst electron transfer occurring at À0.51 V to À0.35 V and the second one at À0.38 V to À0.22 V (using the Ag/Ag + electrode couple as the internal standard), occurring on the C](CN) 2 moieties of the molecule. [20][21][22] The oxidation steps occurring on the aniline moieties are irreversible, as shown in the CV curves. Optimized geometry of the compound calculated from the B3LYP functional 6-31G(d,p) within the DFT level [45][46][47][48] shows the greatly twisted conguration of the charge-transfer moieties and the slight distortion in the OPV 3 bridge.…”
mentioning
confidence: 99%